Shattered dreams : the lost and canceled space missions - Burgess, Colin, 1947- (Outward odyssey : a people's history of spaceflight, 2019)
"'Shattered Dreams' recounts the personal stories and recollections of several men and women who were in line to fly a specific or future spaceflight mission but lost that opportunity due to personal reasons, mission cancellations, or even tragedies"--